Add-on hemoperfusion in SARS-CoV-2-infected pregnant patients: a case series - Supattra Chiewroongroj; Thummaporn Naorungroj; Ranistha Ratanarat (Journal of Medical Case Reports, 2024)
Abstract Background Pregnant women are more likely to have a higher severity of illness after being infected with coronavirus disease 2019 compared with the general population, particularly in the hyperinflammatory phase. However, immunomodulatory drugs are contraindicated and have been associated with an increased risk of fetal abnormalities. Therefore, we are reporting our experience with the use of HA330 hemoperfusion in combination with standard therapy in severe to critical coronavirus disease 2019 cases among pregnant patients. Case presentation From January 2020 to December 2021, four pregnant Thai women were treated with hemoperfusion using a cytokine adsorptive technique. The patients’ ages ranged from 21 to 36 years old, and their gestational ages at the time of admission ranged from 18 to 38 weeks. Two patients required intubation. Extracorporeal blood purification with an adsorptive cartridge (HA330®, Jafron, China) was applied as an adjunctive strategy to standard therapy approximately one week after the onset of symptoms, and most patients received three sessions of hemoperfusion. The baseline C-reactive protein level was greater than 80 mg/dL. The results showed that hemoperfusion could decrease the C-reactive protein level by approximately 80% and improve oxygenation. The newborns were delivered by Cesarean section without complications. Neither mortality nor serious adverse events related to hemoperfusion occurred. Conclusion This report may help ensure the use of the hemoperfusion strategy in pregnant patients during a cytokine storm. However, a larger cohort is needed to confirm its safety and efficacy.